Analyzing Tourism Discourse in the Context of Iranian Promotional Media (LSP International Journal, 2017)
The role of tourism discourse through verbal and visual elements in creating tourists’ destination image has great significance. Most tourism discourse researchers focus on the linguistics and visual parts, but rarely have looked at measuring the elements of destination image associated with tourism discourse. Furthermore, destination image research in the context of some Middle East countries with high potential tourism attractions like Iran has been rather limited. This study tries to address this gap by attempting an in-depth understanding of Iran’s image as a tourist destination worldwide, on the basis of data collected from printed and online brochures and travel guides, and by analyzing the images of the tourists who intended to visit Iran through three open-ended structured questions. The findings of this study revealed that the dominant discourse on tourism texts aim to promote the image of Iran as a safe, peaceful, and a rich land in terms of natural scenery, historical relics, gastronomy, museums and architecture; however, the image of the country has been appeared relatively negative and unfamiliar, as this country are usually classified as Arabs and Iranian culture is not distinctive among most respondents. This research further identifies the distinctive features of Iranian tourism discourse which portray various types of destination images of the country. It is concluded that a realistic communication with prospective tourists through the texts has essential influence on the formation of a positive image and consequently, the success of tourism destinations.